A preliminary screening of potentially antimalarial plants against Plasmodium falciparum in vitro - Khaw, L.T.; Leerach, N.; Yap, N.J.; Jaturas, N.; Mahboob, T.; Tan, T.C.; Dungca, J.Z.; LosBanos, Z.D.; Sitthisak, S.; Chow, S.C.; Lim, Y.A.L.; Sawangjaroen, N.; et al. (2015)
Plasmodium is a blood protozoan parasite that is responsible for malaria. To date, Plasmodium falciparum has shown multi-drug resistance, particularly in Thailand, Myanmar and Malaysia. The aim of the study is to screen the plant extracts that can effectively inhibit P. falciparum 3D7, a common lab strain malaria parasite. Nine plants were collected and processed through maceration using hexane, chloroform and ethanol, resulting in 24 crude plant extracts. Of these, extracts from Artabotrys crassifolius, Pericampylus glacus and Leuconotis eugeniifolia showed promising antiplasmodial activities at IC50 of 15.32 to 39.75 mu g/mL in a modified schizont maturation assay. Further studies are warranted to explore its efficacies and lead compounds of these three plant extracts for the development of antiplasmodial drugs.